Caracterização experimental do equilíbrio de fases da mistura de SF6 e óleo mineral - Miguel Junior, Afonso Ferreira (2020)
Gas-liquid two-phase flow occurs in several industrial applications as the oil industry. Distinct hydrodynamic models were and are still being developed along the last few decades in order to predict the flow patterns in pipelines, the pressure drop and the heat and mass transfer coefficients. The flow patterns cannot only vary depending on different geometrical conditions, but also on different thermodynamic conditions, which determine the phase behavior of the oil-gas mixture. High concentrations of carbon dioxide express a current great challenge in the oil extraction industry. The thermodynamic conditions related to the high pressures found in the reservoirs (higher than the CO2 critical pressure) approximate the mixture to its critical pressure during the extraction. This approximation to the critical point makes it difficult to distinguish the two phases and approximates their densities effecting directly the flow patterns in pipelines. Such conditions are difficult to reproduce in laboratory scale, due to not only the great amount of energy, but also to the unsafe settings it needs. Therefore, a new mixture was proposed to emulate this two-phase density approximation using a high-density gas (SF6) and a low-density liquid (mineral oil) in order to reproduce the conditions in lower pressure, and studying its thermodynamic behavior is key to understanding the flow patterns conditions. In the present research, phase equilibrium data of mineral oil Hydra XP 32 and sulfur hexafluoride (SF6) are determined at temperatures between 10 and 35ºC under different mixture concentrations (from 0.05 to 0.25 of SF6). The isothermal synthetic method was used and three different techniques were compared (visual, ultrasonic and pressure-volume observations) to determine mixture bubble points at different temperatures and point out different mixture behaviors. The main goal of this research was to identify if the binary mixture can be used as a model-fluid for simulating the critical highpressure conditions found in the pre-salt reservoirs, and if só, determine the maximum pressure in which the two-phase system will be maintained under different system temperatures. The data produced by this research will be used on the project of a high-pressure flow loop in order to maintain the mixture in a two-phase flow avoiding three-phase state.